Mentalizing Subtypes in Eating Disorders: A Latent Profile Analysis - Gagliardini, Giulia; Gullo, Salvatore; Tinozzi, Valeria; Baiano, Monica; Balestrieri, Matteo; Todisco, Patrizia; Schirone, Tiziana; Colli, Antonello (Frontiers in Psychology, 2020)
Abstract Background. Mentalizing has been found to be reduced in several mental disorders. Some studies have suggested that Eating Disorders (EDs) may also be associated with impairments in mentalizing. The aim of this work is to investigate the possible presence of mentalizing subtypes in a sample of patients with eating disorders (EDs). Method. A sample of patients with eating disorders (N = 157) completed a battery of measures assessing mentalization and related variables including the Reflective Functioning Questionnaire (RFQ), the Difficulties in Emotion Regulation Strategies (DERS), the Interpersonal Reactivity Index (IRI). Clinicians rated patients in relation to mentalization imbalances, prementalizing modes and attachment by using the Mentalization Imbalances Scale (MIS), the Modes of Mentalization Scale (MMS) and the Adult Attachment Questionnaire (AAQ). A Latent Profile Analysis was conducted to test the possible presence of different subgroups. MANOVA was used to test the possibile differences between the four mentalizing profiles in relation to emotion dysregulation (DERS), empathy (IRI) and adequate and impairments in mentalizing (MMS and RFQ). Results. Latent Profile Analysis suggested the presence of four different profiles in relation to impairments in the dimensions of mentalization: 1) Affective/Self/Automatic imbalances 2) External imbalance 3) Cognitive/Self/Automatic imbalances 4) Cognitive/Other/Automatic imbalances. Patients belonging to Profile 1 are characterized by the prevalence of affective mentalization that overwhelms the capacity to reflect on mental states with an imbalance on the self dimension; Profile 2 patients are focused on the external cues of mentalization; Profile 3 patients are characterized by an over-involvement on the cognitive and self facets of mentalization with an impairment in adopting the other mind perspective; Profile 4 patients has an excessive focus on the others and deficits in self reflection. These profiles were heterogeneous in terms of EDs represented in each group, and presented significant differences on various variables such as attachment style, emotion dysregulation, empathy, interpersonal reactivity and reflective function. This study represents so far the first work that confirms the presence of different mentalizing patterns in ED patients. Conclusions. ED patients can be classified in relation to impairments in different dimensions of mentalization above and beyond ED diagnosis.